2021
DOI: 10.1128/aac.01196-20
|View full text |Cite
|
Sign up to set email alerts
|

Pretomanid Pharmacokinetics in the Presence of Rifamycins: Interim Results from a Randomized Trial among Patients with Tuberculosis

Abstract: Shorter, more potent regimens are needed for tuberculosis. The nitroimidazole pretomanid was recently approved for extensively drug-resistant tuberculosis in combination with bedaquiline and linezolid. Pretomanid may also have benefit as a treatment-shortening agent for drug-sensitive tuberculosis. It is unclear how and if it can be used together with rifamycins, key sterilizing first-line drugs. In this analysis, data were pooled from two studies: the Assessing Pretomanid for Tuberculosis (APT) trial, in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In contrast, the pretomanid–rifampin combination likely decreased pretomanid exposures such that its effect on time-to-culture conversion in liquid culture was observed as a nonsignificant trend. The published interim pharmacokinetic analysis supports this hypothesis, given that pretomanid exposure as measured by the area under the concentration time curve was 44.4% lower in the pretomanid–rifampin arm than in the pretomanid–rifabutin arm, driven by an 80% increase in clearance ( 11 ). Another potential explanation for the observed differences in efficacy, as raised by the authors, may be that rifabutin exhibited different efficacy than rifampin; however, a previous systematic review did not show a difference between these rifamycins with respect to sputum culture conversion, cure, or relapse ( 12 ).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…In contrast, the pretomanid–rifampin combination likely decreased pretomanid exposures such that its effect on time-to-culture conversion in liquid culture was observed as a nonsignificant trend. The published interim pharmacokinetic analysis supports this hypothesis, given that pretomanid exposure as measured by the area under the concentration time curve was 44.4% lower in the pretomanid–rifampin arm than in the pretomanid–rifabutin arm, driven by an 80% increase in clearance ( 11 ). Another potential explanation for the observed differences in efficacy, as raised by the authors, may be that rifabutin exhibited different efficacy than rifampin; however, a previous systematic review did not show a difference between these rifamycins with respect to sputum culture conversion, cure, or relapse ( 12 ).…”
mentioning
confidence: 83%
“…Its substitution for ethambutol in drug-susceptible TB, however, does have caveats; pretomanid has a known drug–drug interaction with rifampin, a potent inducer of the cytochrome P450 system, which decreases pretomanid plasma concentrations. Interim pharmacokinetic analysis of pooled data from the APT trial and the AIDS Clinical Trials Group A5306 trial confirmed that rifabutin averts the drug–drug interaction with pretomanid ( 11 ).…”
mentioning
confidence: 93%
“…SimpliciTB is the continuation of the STAND trial that was changed from PaMZ into BPaMZ when the results came available of the NC005 trial. Further trials with PA are the phase 3 ZeNix trial (aimed to reduce linezolid toxicity) and the phase 2B APT trial evaluating PA added to a first-line regimen with either rifampicin or rifabutin, isoniazid, and pyrazinamide [ 63 ].…”
Section: New Drugsmentioning
confidence: 99%
“…A recent study suggests that this increased exposure in the fed state may be leveraged to negate the reduction expected with co-administration of rifampin. 63 …”
Section: Pharmacology and Toxicologymentioning
confidence: 99%